Identification of a key environment-responsive gene mediating environmental impact on postmenopausal osteoporosis - Wan, Baicheng; Zhou, Junhong; Teng, Yilin; Tong, Ye; Zong, Shaohui (Frontiers in Public Health, 2025)
BackgroundOsteoporosis is a multifactorial disease influenced by genetic, environmental, and metabolic factors. AKT serine/threonine kinase 1 (AKT1), a central regulator of cellular survival and metabolism, has been implicated in bone remodeling, yet its precise role in osteoporosis remains unclear.MethodologyGene expression analysis and molecular docking simulations were performed to identify key pathways and interactions involving bisphenol A (BPA) and AKT1. Molecular dynamics simulations further assessed the stability of BPA-AKT1 binding. Experimental validation was conducted using bone marrow-derived macrophages (BMMs) treated with BPA. Osteoclastogenesis was evaluated through TRAcP staining, and AKT1 expression was analyzed via real-time PCR. Protein-level validation of AKT1 phosphorylation was performed using Western blot analysis to confirm its activation during osteoclast differentiation.ResultsComputational analyses identified AKT1 as a key mediator linking BPA exposure to bone remodeling pathways. Molecular docking revealed strong interactions between BPA and AKT1, supported by molecular dynamics simulations showing stable binding. Experimental assays demonstrated that BPA significantly enhanced RANKL-mediated osteoclastogenesis, upregulated AKT1 mRNA expression, and promoted AKT1 phosphorylation. These findings indicate that BPA promotes bone resorption through AKT1 activation, potentially contributing to osteoporosis pathogenesis.ConclusionAKT1 emerges as a critical node connecting environmental pollutants like BPA to bone health, highlighting its potential as a therapeutic target. These findings underscore the complexity of osteoporosis pathophysiology and the importance of mitigating environmental pollutant exposure.